Evaluating the effects of taxing the remittances of skilled workers on capital accumulation and aggregate income using an overlapping generations model1 - Rivera, John Paolo R. (Animo Repository, 2013)
Labor migration has sizable economic impacts specifically to labor-sending countries such as the Philippines, which can alter the economy's production structure and redirect the country's comparative advantage. The exodus of highly trained professionals, without replacement, will lead to brain drain in a country with limited access to quality higher education especially if the education costs of these professionals have been subsidized by the state; hence, a substantial loss to society is incurred. Likewise, the training costs of replacements can be reasonably substantial and may cause the reduction of the productivity of workers left behind. Thus, this study developed an Overlapping Generations (OLG) Model on the Philippine context that will discuss the management of skilled labor migration and assessing the macroeconomic effects it entails. By hypothetically incorporating how a tax on the income of skilled migrant workers abroad specifically to those schooled in state universities and colleges (SUCs), as proposed by Bhagwati (1976), affects the macroeconomy, this study provides an insight on the efficacy of its implementation. Simulation results have shown that imposing the brain drain tax can enable the economy to achieve a higher steady state capital stock and steady state aggregate income paths on the condition that the government will not spend all the revenues from the brain drain tax on one generation.